The Role Of Citizenship Education Learning In Forming Students' Nationalism Attitudes In Grade VIII - Agnes Lorenza Parapat; Hotmaida Simanjuntak; Rince Marpaung; Lukman Pardede; Monalisa Siahaan (STABN RADEN WIJAYA WONOGIRI, 2023)
This study aims to explore the extent to which Civic Education (PPKn) contributes to fostering nationalism among eight-grade students at SMP Negeri 2 Pancur Batu. The research is grounded in the urgency of instilling nationalist values to face the challenges of globalization, which threatens the national identity of the younger generation. A qualitative approach was employed, with data collected through observation, interviews, and documentation. The findings reveal that Civic Education plays a significant role in shaping students' nationalist attitudes. Teachers actively engage in delivering contextually relevant material and apply interactive teaching methods. Several factors influence the development of nationalism in students, including the role of teachers, teaching strategies, family environment, peer influence, and social media. Overall, students exhibit a relatively strong sense of nationalism, reflected in their participation in school activities with national themes, respect for national symbols, and an appreciation for diversity. In conclusion, Civic Education contributes meaningfully to the internalization of nationalist values among students. Therefore, synergy among teachers, parents, and schools is essential to strengthen students' nationalism so that they grow into citizens who love their country and uphold Pancasila values.